Study of thermal ageing effects on Rh coating's mechanical performance upon CuCrZr substrate through modeling and experimental methods. (August 2018) - Chen, Z.X.; Hillairet, J.; Turq, V.; Song, Y.T.; Laloo, R.; Vulliez, K.; Bernard, J.M.; Yang, Q.X.; Hernandez, C.; Ferreira, L.; Fesquet, F.
Abstract: Rhodium (Rh) coating on CuCrZr substrate is a promising material option for optical, structural and electrical applications on nuclear fusion reactors. For these applications, Rh coated CuCrZr components subject to long time of thermal ageing due to pre-treatment or normal operation condition. In this paper, both finite element method (FEM) and experimental method were applied to investigate the effects of thermal ageing on mechanical performance of Rh coating after 250 °C, 500 h baking in vacuum. Based on FEM analysis, thermal stresses which concentrate at Rh coating interface is the main source of cracking, and such stresses can be minimized efficiently by introducing a 0.5 μm Au interlayer into the coating layer structure. According to thermal ageing experiments, through-thickness cracking in the Rh coating due to thermal stress releasing and voids generated at the Rh bonding interface caused by Kirkendall effect were the main micro-structure changes in the coating system. The solid-solution hardening caused by significant Cu diffusion into Rh is the dominant factor that affected the Rh coating's hardness. The existing of large amount of cracks in the Rh coating and voids at the Rh coating interface deteriorated the adhesion performance of Rh on CuCrZr substrate by 30%. Highlights: Applying of Au interlayer to decrease Rh coating's thermal stress was modeled. Electroplated Rh showed good thermal stability in hardness and crystallite size. Diffusion phenomenon at Rh/Cu interface impaired the Rh adhesion significantly.